Siyasal söylemde mağduriyet - Oztin Passerat, Duygu (Border Crossing, 2016)
Bir söylemin varlığı üç bileşene bağlıdır: söylemin kaynağı olan konuşucu, alıcı ve söylemin kendisi. Söyledikleriyle karşısındakini etkilemek ve inandırmak için, konuşucunun içten ve dürüst olması, dinleyicinin duygularına seslenmesi ve aynı zamanda da doğru ve tutarlı gerekçelerden oluşan bir dil kullanması gereklidir. Duygulara seslenen söylemler “yanlış gerekçelendirme” ya da “hatalı gerekçelendirme” (ing. fallacies, fr. paralogisme) olarak adlandırılmış ve mahkum edilmiştir. “Karşımızdakini söylediklerimize inandırmak için sadece akla değil, o’nun duygularına dokunmak ya da seslenmek gerekir” düşüncesi de başkaları tarafından ortaya konmuş ve benimsenmiştir. Çalışmamızda, alıcının acıma duygularını (fr. appel à pitié) harekete geçirerek kendisine sempati ya da ilgi duymasını sağlamak üzerine kurulu olan mağduriyet söyleminin (fr. discours victimaire) sözcelemsel, söylemsel ve de sözbilimsel özelliklerini inceleyerek “mağduriyet söylemi siyasal söylemde nasıl ortaya konmaktadır? Bu söylemin ortaya konması siyasal aktörlerin inandırıcıklarında ya da gerekçelendirmelerinde (fr. argumentation) nasıl rol oynamaktadır? sorularına yanıt arayacağız. Çalışmanın bütüncesini, T.C. Cumhurbaşkanı’nın çeşitli zaman aralıklarıyla ortaya koyduğu söylemler oluşturacaktır. EXTENDED ABSTRACT IN ENGLISH Victimization in the political discourse Extended Abstract Discourse consists of three components: source of the discourse: the addresser, addressee, and the discourse itself. Aristoteles, hence, identified the rhetorical evidences as ethos, pathos and logos concerning these three components. In other words, the addresser/speaker should be sincere and honest, appeal to the emotions of the addressee and use the language consisting of consistent and accurate argumentations to be able to have an impact on the addressee and persuade target audiences. The discourse appealing to emotions was called as fallacy and condemned by first Plato, the teacher of Aristoteles, then by Hamblin (Fallacies, 1970) and later by the contemporary linguists and argumentation scholars. However, Aristoteles and some contemporary linguists such as Plantin, Amossy, and Charaudeau have adopted the idea that it is necessary to touch upon not only the addressee’s minds, but also their emotions to make them believe what we talked. Because the discourse including the addressee’s emotions is more persuasive and effective. In this study, we aim at analysing the rhetorical, discursive and semantic characteristics of victimization discourse based on activating the humane sentiment of the listeners and arousing interest and sympathy. We are going to try to answer these questions like; how does the victimization discourse present in the political discourse? How does this discourse have a role in the persuading and the argumentation of the politicians to the target audiences? One of the most important manner of discourses is the political discourse that makes us believe what we talk by activating the emotions such as compassion and pathos of the listeners. The usage of victimization in the political discourse means the utterance of the political actor in his speeches about the injustices made to him or the idea he is representing. As for the politician leader of the opposition, he develops his political discourse by complaining to voters about ruling party’s implementations. If the politician is in the ruling party, he complains about the oppression and the interdict made to him or the idea he is representing. The corpus of the study consists of the certain political discourses of President of Republic of Turkey. While he was listing the factors that caused his victimization or the people that behaved unjustly toward him, he listed by beginning from collective subject to individual subject in the subject of political discourse. In other words, the bedeviled people are firstly Saidi Nursi and his idea, then turbaned girls and finally himself as subject of discourse. This list reduces the subjectivity of discourses subject: the bedeviled. At the same time, it has been effective in the presentation of the victimization on the idea he is representing not himself. For this reason, aggrieved party is firstly third-person singular, then first-person singular. Regarding the perception in the listeners or voters by using this discourse of political subject, he aimed at creating a character: brave, fearless hero, ready for going to a prison, even dying for his idea in face of the listeners by using bedeviled political subject with the discursive strategies as stated above. His receiving into prison is so important that he showed this experience as a reason by emphasizing that we are here by wearing our shrouds. Thus, he seems to be as a leader like honourable, brave, religionist and principled. He activates the sentiments of the listeners not only pathos but also highly sensitive religious sentiments. If we think about his discourse He was oppressed, despised, even ignored for a while in Turkey, he has been in power since a long time; the subject of this sentence is now president. We can conclude that victimization in the political discourse is very important, even a discursive irreplaceable strategy.